Patterns of family–school environment influence depressive symptoms among adolescents in China: the mediating role of resilience - Liao, Suqun; Wang, Dongfang (Frontiers in Psychiatry, 2025)
BackgroundPrevious studies have shown that both family and school environments are significantly associated with depressive symptoms in adolescents. However, it remains unclear how specific patterns of the family–school environment influence later depressive symptoms and what mechanisms may explain this relationship.MethodsA total of 11860 adolescents completed web-based surveys during two periods: 21 April to 12 May 2021 (Time 1, T1) and 17 to 26 December 2021 (Time 2, T2). Participants reported on sample characteristics, family function, school climate, resilience, depressive symptoms, and negative life events. Latent profile analysis was used to identify profiles of family–school environment, and mediation analyses were conducted to examine whether resilience mediates the associations between these environmental profiles and depressive symptoms.ResultsFour distinct family–school environment profiles were identified: (1) family dysfunction–poor school climate (32.2%), (2) good family function–good school climate (27.8%), (3) good family function–poor school climate (26.6%), and (4) family dysfunction–good school climate (13.4%). Compared with the “good family function–good school climate” group, participants in the other three profiles showed higher levels of depressive symptoms at T2, mediated by lower levels of resilience.ConclusionsThese findings highlight the importance of monitoring adolescents’ perceptions of their family and school environments in early depression screening. Timely and targeted interventions aimed at enhancing resilience may be beneficial for adolescents in high-risk environmental profiles.